Pengaruh Adversity Quotient Dan Spiritual Quotient Terhadap Kinerja Guru Dan Karyawan - Tadjoer Ridjal; Mochamad Syauqhy Radjfi; Heni Setyowati (FAI- Undar, 2022)
In teaching and learning activities, the performance of teachers and employees is one of the most important factors. However, this performance problem is of course also influenced by many factors, one of which is Adversity Quotient and Spiritual Quotient. So in this study, the positive and significant influence on Adversity Quotient and Spiritual Quotient on the performance of teachers and employees at SMK Madania Sidoarjo will be tested. This research was conducted with a quantitative approach, with a non-experimental design. With a population of 20 teachers and employees at SMK Madania Sidoarjo. The instrument used is a questionnaire, with multiple linear regression data analysis techniques. The test results show that the Adversity quotient has a significant effect on the performance of teachers and employees at SMK Madania Sidoarjo. This is evidenced by the results of the t test, where the sig value obtained is 0.006, where the number is smaller than the probability value of 0.05 (sig 0.006 < 0.05). Variable X1 has tcount = 3.167 and ttable = 2.634, so the conclusion that can be drawn is that variable X1 has a contribution to Y. Then based on multiple regression analysis, the B value on the adversity quotient is 0.333, which means the influence of the adversity quotient on teachers and employees of SMK Madania by 3.33%. While Spiritual quotient has a significant effect on the results of the t test, where the sig value obtained is 0.003 smaller than the probability value of 0.05 (sig 0.003 < 0.05), with tcount = 3.518 and ttable = 2.634, then based on multiple regression analysis, The value of B on the adversity quotient is 0.479, which means that the influence of the adversity quotient on teachers and employees of SMK Madania Sidoarjo is 4.79%. Adversity quotient and spiritual quotient together have a positive and significant effect on the performance of teachers and employees at SMK Madania Sidoarjo, based on the sig value. obtained is 0.000, where the value is smaller than the probability value of 0.05. Meanwhile, based on the R2 value obtained, which is 0.928, it can be concluded that the two variables have an effect on Y of 9.28. Or there is a significant and simultaneous influence between adversity quotient and spiritual quotient on the performance of teachers and employees at SMK Madania Sidoarjo.